Pitting Corrosion of Ni3(Si,Ti)+2Cr Intermetallic Compound at Various Chloride Concentrations - Gadang Priyotomo; Pius Sebleku; Yasuyuki Kaneno (International Journal of Science and Engineering, 2014)
The pitting corrosion of Ni3(Si,Ti) with 2 at% Cr containing two regions of a Ni3(Si,Ti) single-phase of L12 structure and a mixture phase of of (L12 +Niss) was investigated as function of chloride concentrations by using a polarization method, scanning electron microscope and energy dispersive X-Ray spectroscopy in neutral sodium chloride solutions at 293 K.  The pitting corrosion of Ni3(Si,Ti) with and without the addition of aluminium and type C276 alloy were also studied under the same experimental condition for the comparison.  The pitting potential obtained for the Ni3(Si,Ti) with 2 at% Cr decreased with increasing chloride concentration.  The specific pitting potentials and the pitting potentials were decreased in the order of C276 alloy > Ni3(Si,Ti) > Ni3(Si,Ti) + 2Cr > Ni3(Si,Ti) + 4Al, which means that the pitting corrosion resistance of Ni3(Si,Ti) with 2 at% Cr was higher than Ni3(Si,Ti) with 4 at% Al, but lower than that of Ni3(Si,Ti).  A critical chloride concentration of Ni3(Si,Ti) with 2 at% Cr was found to be higher than that of Ni3(Si,Ti) with at% Al. In addition, the presence of high concentration for oxygen indicates the occurrence of pit formation.